Mass‐Manufactured Beam‐Steering Metasurfaces for High‐Speed Full‐Duplex Optical Wireless‐Broadcasting Communications. Issue 6 (28th December 2021) - Tao, Jin; You, Quan; Li, Zile; Luo, Ming; Liu, Zichen; Qiu, Ying; Yang, Yan; Zeng, Yongquan; He, Zhixue; Xiao, Xi; Zheng, Guoxing; Yu, Shaohua
Abstract: Beam‐steering devices, which are at the heart of optical wireless‐broadcasting communication links, play an important role in data allocation and exchange. An ideal beam‐steering device features large steering angles, arbitrary channel numbers, reconfigurability, and ultracompactness. However, these criteria have been achieved only partially with conventional beam‐steering devices based on waveguides, micro‐electricalmechanical systems, spatial light modulators, and gratings, which will substantially limit the application of optical wireless‐broadcasting communication techniques. In this study, an ultracompact full‐duplex metabroadcasting communication system is designed and experimentally demonstrated, which exhibits beam steering angles up to ±40°, 14 broadcasting channels with capacity for downstream and upstream links up to 100 and 10 Gbps for each user channel, three operating modes for flexible signal switching, and metadevice dimensions as small as 2 mm × 2 mm. In particular, the beam‐steering metadevices are mass‐manufactured by a complementary metal–oxide–semiconductor (CMOS) processing platform, which shows their potential for large‐scale commercial applications. The demonstrated metabroadcasting communication system merges optical wireless‐broadcasting communications and metasurfaces, which reduces the complexity of beam‐steering devices while significantly increasing their performance, opening up a new avenue for high‐quality optical wireless‐broadcasting communications. Abstract : Assisted by an silicon‐on‐isolator‐based metasurface that can be mass‐manufactured by the complementary metal–oxide–semiconductor (CMOS) process, an ultracompact prototype for full‐duplex metabroadcasting communications is demonstrated, which shows beam‐steering angles up to ±40°, 14 broadcasting channels with capacity for downstream and upstream links up to 100 and 10 Gbps for each user channel, and three operating modes for flexible signal switching.